Impact of foliar application of ascorbic acid and α-tocopherol on antioxidant activity and some biochemical aspects of flax cultivars under salinity stress (2015)
The interactive effects of saline water (2000, 4000 and 6000 mg/l) and foliar application of 400 mg/l of ascorbic acid (Asc) or α– tocopherol (α-Toco) on three flax cultivars (Sakha 3, Giza 8 and Ariane) were conducted during two successive seasons 2011/2012 and 2012/2013. The results showed that total soluble carbohydrates, free amino acids and proline contents were significantly increased with increasing salinity levels in the all three tested cultivars except free amino acid content of Giza 8 which showed insignificant decrease. While, nucleic acids (DNA and RNA) showed significant decreases compared with the corresponding control. Moreover, applications of vitamins (Asc or α-Toco) as foliar spraying increased all mentioned contents compared to the corresponding salinity levels. On the other hand, lipid peroxidation and activity levels of polyphenol oxidase, peroxidase and catalase enzymes showed significant increases with increasing salinity levels of all tested three cultivars, while the behaviour of superoxide dismutase activity showed an opposite response as compared with the control in Sakha 3 and Giza 8. Treatments with Asc or α-Toco induced significant reduction in lipid peroxidation and activities of polyphenol oxidase, peroxidase of the all three tested cultivars. Meanwhile, superoxide dismutase increased in all three cultivars, and catalase activities increased only in Sakha 3 cultivar under salt stress as compared with reference controls. Some modifications are observed in protein patterns hence some proteins were disappeared, while certain other proteins were selectively increased and synthesised of a new set of proteins were induced, some of these responses were observed under treatments and salinity, while others were induced by either treatments or salinity.